Pengaruh Pembiayaan Mudharabah, MusyarakahDan Non Performing Financing (NPF) TerhadapProfitabilitas (ROE) Pada Bank Umum Syariah Di Indonesia - Kusmiati Kusmiati; Muhammad Luthfi; Indah Lia Puspita (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2016)
This study aimed to test whether a variable Mudaraba, Musharaka financing and NonPerforming Financing (NPF) Influence To Profitability In Syriah Commercial Bank in Indonesia. Thesample used in this study is Bank Sharia which displays quarter financial statements during the period2010-2014. The analysis in this study using multiple linear regression analysis to tRefineries on the data in this study using SPSS 16.0 (Statistical Package For The Social Science).Based on the results of the calculations on simultaneous test values obtained Fcount 10.945 and thevalue of P-Value (0,000), Value P-ValuePerforming Financing (NPF) significant effect on profitability, while partially on Financing Mudhabah(0.05), the Musharaka financing variable has no effect on the profitability of Islamic Banks with tcountsignificant impact on profitability is negative with tcount(0.05).